Możliwości komunikacyjne dziecka z zespołem Aspergera - Konieczna, Iwona (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
Last time a huge progress of researches regarding communication possibilities of children with Asperger’s syndrome can be noticed. Despite of this, the knowledge concerning this subject seems to be insufficient. There is also indisputable fact, that communication both on linguistic and non – linguistic level is incorrect. Disorders in this area might have different nature. Some children can be on a satisfactory level in linguistic area, some did not carve communication skills in sufficient level and it is hard to predict their development in this area. Additional difficult are huge differences between development of their communication skills. Communication ability is not only a part of socialization but also impacts on emotional and cognitive development, mainly because of it allows to extend area of experiences and understandding of world and people. Abnormalities which can be seen in development of children with Asperger’s syndrome dispose to think what kind of methods can be used in order to make efficient their functioning in social area.